Eradication of poverty South Asia's call for joint responsibilities. - Eurostep South Asia Partner Consultation on Poverty Eradication and Quality of Aid in South Asia (2000 Manesar, India); HIVOS (Organization). South India Regional Office; EUROSTEP (Organization). (Bangalore Humanist Institute for Co-operation with Developing Countries, Netherlands, India Regional Office, 2000)
Proceedings of Eurostep South Asia Partner Consultation on Poverty Eradication and Quality of Aid in South Asia, held at Manesar, September 26-29, 2000.
"European Solidarity Towards Equal Prticipation of People"--Cover.
Includes bibliographical references.
CSSP-6306 donated by The Rotary Club of Beaverton, Oregon, United States of America.
Keywords: Poverty -- South Asia -- Congresses; Economic assistance, European -- South Asia -- Congresses